Hydrological stress as a limiting factor of the invasion of Limnoperna fortunei (Dunker, 1857) in the Upper Paraná River (Brazil) - Campos,Mônica de Cássia Souza (2012)
Limnoperna fortunei (Dunker, 1857), is an asiatic mussel that arrived in South America in 1991. Since 2004, we have noticed that the advance of this species in the lower Paranaíba River, a tributary of the Upper Paraná River, is slow when compared to the average speed of 240 km/year in the Paraná River (middle and lower course). AIM: The goal of this work is to understand what factors are limiting the spread of L. fortunei in this stretch of the Paranaíba River. METHODS: Its occurrence and dispersion were sampled twelve times between March 2006 and November 2007 in the Paranaíba River, including the São Simão hydroelectric reservoir. Physicochemical characteristics of the water were analysed, and a Stream Length-Gradient Index calculated for the study area. RESULTS: Adult mussels were easily found attached to the hulls of barges that travel on this stretch of the Paraná-Tietê waterway and on vessels that were docked in the harbours of grain exporters located in São Simão (GO). However, no larvae or adults were found near the harbours or upstream from them at the São Simão hydroelectric reservoir. The pH and concentration of calcium and dissolved oxygen values among lotic habitats and the reservoir were similar: DO values were close to 7 mg.L-1, the average pH was near 7, average values of total Ca ranged between 4 and 6 mg.L-1 and the chlorophyll-a levels were not restrictive to the mussel. CONCLUSION: Physical and chemical water parameters show that habitats were suitable for establishment of the mussel. In addition to a low pressure of propagules, this paper proposes some hydrological variables, such as the energy of the fluvial stretches, expressed by the Stream Length-Gradient Index and changes in flow downstream of the dam as barriers to the establishment of the species, discouraging larval settlement, and decreasing survival and recruitment.